Effectiveness Of Administrative Sanctions Enforcement In Code Of Notary (A Studi In Cirebon) - Maulana Agung; Ahmad Mustarsidin; Gunarto Gunarto (Jurnal Akta, 2018)
In running position, besides bound by the Law Notary, the Notary is also bound by the Notary Code, created by the organization Indonesian Notary Association (INI). Notary supervision carried out by the Minister of Law and Human Rights by establishing a Notary Supervisory Council, and the Organization of Indonesian Notary Association established the Honorary Board of the Notary. The purpose of this study is to analyze the type of Code violations that occurred in Cirebon, analyze the types of sanctions that are applied, and analyze the effectiveness of administrative sanctions were applied in establishing the Notary Code. The results showed of some types of provisions Notary Code, violations that occurred in the district of Cirebon include price competition, and the use of intermediaries in getting clients. Based on the results of this study concluded that several factors causing these violations such as contradictory rules with conditions on the ground, a notary referred to as public official, but are forbidden to promote themselves, as officials, but not paid by the State as public officials more, while the number of Notaries every year increases, there is competition between them, caused intentionally or not unethical Notary. In addition, the sanctions only administratively, causing frequent violations and lack of deterrent effect,Keywords: Code of Notary; Effectiveness; Sanctions.